Recent Advances in Agricultural Precision Irrigation Method Based on Intelligent Control Algorithm - Majewski, Adam; Brzozka, Bartlomiej (Journal of Intelligent Information and Communication, 2025)
As the global water shortage problem is becoming more and more serious, precision irrigation in agriculture has become a key technology to improve the efficiency of water utilization, guarantee food security and environmental protection. The continuous development of intelligent control algorithms provides new solutions for agricultural precision irrigation. This paper systematically analyzes the research status, technical applications, problems and future development trends of agricultural precision irrigation methods based on intelligent control algorithms through literature review. It is found that a variety of intelligent control algorithms show broad application prospects in agricultural precision irrigation, but still face some technical challenges and practical application limitations. Future research should further optimize the performance of algorithms, strengthen the integration of multiple technologies, and promote the popularization and application of smart irrigation technology.